Discourse Structure Analysis of Hasanak-e-Vazir’s Hanging Tale: A Study based on Van Dijk’s (2007) Socio-Cognitive Approach - Nader Abyar; Mousa Ghonchepour; Zahra Iranmanesh (مطالعات زبان‌‌ها و گویش‌های غرب ایران)
Critical discourse analysis affects the speakers' comprehension of social, cultural and political issues by uncovering the underlying structures of messages. This descriptive-analytical study investigates the hanging tale of Hasanak-e-Vazir based on Van Dijk’s (2007) socio-cognitive approach to clarify the functional relation between language, ideology, power and dominance in social and political context of Bayhaqi's period. The study’s sampling is purposeful and samples are taken from Hasanak’s tale based on the research-made worksheet. Data analysis showed that the semantic level elements of categorization, polarization, hyperbole, disclaimer, vagueness, empathy, distance, euphemism and rhetoric were used. In argumentative level, the categories of evidence, reference, comparison, and explicitness were used. The findings indicate that Bayhaqi refers to the society with us-them polarization performed based on the power groups. Moreover, categorization, disclaimer and hyperbole were used to express the good characteristics of in-group (positive self-representation) and bad social actions of out-group (negative-other representation). Ambiguity quantifiers show the opacity in interpersonal relations and dark situation of Bayhaqi's period. The euphemism softens the disorder situation and indicates the violent situation of those days. In stylistic level, metaphor, metonymy and contrast and in syntactic level, word order movement and modality categories were used to show us-them polarization. Introduction Language is used to exchange information and to express feelings and issues. When an individual reads a text or hears messages, they not only try to comprehend the meanings of the words but also seek to understand the intentions of the speakers or writers. Critical discourse analysis examines the relationship between discourse and social power to uncover interpersonal relations and reveal underlying messages. Since no text is neutral and all texts are produced within specific contexts—including elements such as agents, actors, time, place, manner, and reasons for actions—critical discourse analysis helps researchers explore the deeper layers of texts. Bayhaqi's History is a poetic-historical work in which the writer narrates the history of Hasank-e-vazir. Hasank-e-vazir was the last minister of Mahmud Gaznavi and was executed by Masud Gaznavi for being a Qarmatian (Bayhaqi, 1992: 136). This study aims to reveal the hidden relationships among discourse elements, events, and the social and cultural structures of the text, and to understand how these relationships challenge power dynamics for a better understanding of the social and political context during Bayhaqi's time. The tale of Hasank-e-vazir, like other stories, is shaped by the society of the time and is embedded in the social institutions of that era. Since this event has not been analyzed using van Dijk's approach (2007), examining it will clarify the beliefs and ideas of the participants or social actors. Additionally, this study will uncover the underlying meanings of the discourse structures employed by the actors in their interactions with others or with different groups. Understanding the social conditions and power representations of Bayhaqi's time makes the study of this occurrence particularly significant. Methods This study is a descriptive-explanatory article based on the nature and objectives of the data, as it explores power strategies and inequality through the analysis of language and lexical style. Sampling was purposeful, and the data were extracted from the account of the hanging of Hasank-e-vazir. The data include words and clauses analyzed using van Dijk’s (2007) power tools to illustrate how Bayhaqi employs these strategies to depict the polarization of a positive self-image and a negative other-image. To determine the ideological nature of this story, self and other schemas were identified and classified to clarify the images that each group had of itself and the other participants in the discourse. This involved identifying and analyzing the semantic, stylistic, rhetorical, argumentative, syntactic, propositional, action, and interaction levels. Based on the elements and categories of each level, the discourse was analyzed using a researcher-developed checklist of discourse analysis strategies tailored to different levels. Results and Discussion The hanging tale of Hasank-e-vazir was analyzed according to the various levels and categories introduced by van Dijk (2007) to elucidate the power relations during Bayhaqi’s era, particularly those that led to Hasank-e-vazir’s downfall. Additionally, examining this socio-political and cultural event sheds light on the feelings, thoughts, and beliefs of the participants of that time. At the semantic level, the analysis revealed categories such as categorization, polarization, hyperbole, disclaimer, vagueness, empathy, distance, euphemism, and rhetoric. At the argumentative level, categories of evidence, reference, comparison, and explicitness were identified. In the stylistic and rhetorical levels, techniques like deletion, metaphor, sarcasm, metonymy, and contrast were noted, while at the syntactic and propositional levels, categories of word order movement and modality were employed. In the tale, Bayhaqi utilizes semantic and syntactic categories to highlight the polarized society of “us” versus “them.” The “us” group includes Bayhaqi, Hasank-e-vazir, Khaje Meymandi, the wise, and ordinary people, while the “them” group comprises Busahl Suzani, Sultan Mahmud, Ali Rayez, and the Baghdad Caliph. The “us” group is portrayed positively, whereas the “them” group is depicted negatively. Hyperbole is used to emphasize the virtues of the in-group and the reprehensible actions of the out-group. The polarization and categorization are evident through positive self-representation and negative other-representation in the disclaimer strategy. Vague quantifiers highlight the lack of transparency in interpersonal relations and the obscured aspects of society during Bayhaqi’s time. This vagueness also reflects the issues of powerful groups that the common people are unaware of. The empathy strategy demonstrates the common people's feelings toward Hasank-e-vazir (the in-group) and their objections to the actions and roles of the out-group in creating the current situation. Euphemism is employed to soften the harsh and confusing societal conditions. Marked (topicalized and inverted) clauses were used to enhance the impact of the speech on the audience. This style directs the audience's attention more towards Hasank and his associates (the in-groups) than towards the out-groups. Topicalized verbs at the beginning of clauses persuade readers to accept the narrative. The choice of words in discourse reflects the attitudes and beliefs of participants. Words represent cultural, political, and social perspectives and are used to interact, think, and delineate the distance between in-groups and out-groups. Interactions among different participants shaped the discourse surrounding Hasank. The actions taken during these interactions resulted from one group's dominance over another. This dominance was linked to power dynamics among the groups and participants. During Sultan Mahmud's reign, Hasank was powerful, while under Masud’s rule, Busahl Suzani held power and controlled events. Thus, the tale of Hasank represents a power struggle between two groups. This discourse, driven by power, serves as a means for one group to assert dominance over the other, rather than being founded on an ideological basis. Conclusion The tale of Hasank-e-vazir's hanging was analyzed using van Dijk's (2007) theory, which examines data through various levels—syntactic, semantic, stylistic, argumentative, action, and interaction—and explores the relationship between macro and micro levels to derive reliable findings. The results indicated that Bayhaqi employed several strategies to convey the message of this discourse: